Perceived stress and allostatic load: Results from the All of Us Research Program - Faith Morley; Lauren Mount; Anjile An; Erica Phillips; Rulla M. Tamimi; Kevin H. Kensler (PLoS ONE, 2025)
The rising prevalence of individuals reporting extreme stress has major public health implications as it increases vulnerability to accelerated premature biological aging, thus increasing risk of chronic disease. To examine the impact of stress on premature biological aging, we assessed the association between exposure to increased stress, quantified by the Perceived Stress Scale, and odds of high allostatic load (AL). To illuminate previously unexplored socio-contextual factors, we controlled for self-reported individual and neighborhood social determinants of health that included discrimination, loneliness, food insecurity, neighborhood disorder, and neighborhood social cohesion. We utilized a cross-sectional design to examine the association between perceived stress and AL among 7,415 participants ages 18–65 in the All of Us Research Program, who enrolled from 2017–2022. We used logistic regression to evaluate the association between stress and high AL, controlling for sociodemographic factors and self-reported social determinants of health. Participants who were younger, receiving Medicaid, or Hispanic had increased prevalence of high stress. High stress was associated with elevated odds of high AL in age and sex-adjusted models (OR=2.18, 95%CI = 1.78, 2.66, high stress vs. low), an association which remained significant after adjusting for social determinants of health (OR=1.29, 95%CI = 1.01, 1.65). Using restricted cubic splines, high stress was significantly associated with increased odds of high AL, even after controlling for upstream individual and neighborhood-level determinants of health. While individuals living below the medium poverty-to-income ratio demonstrated little appreciable association between high stress and increased odds of high allostatic load, those living above the median poverty-to-income ratio reporting increased stress appeared to have increased odds of high allostatic load. Through addressing the upstream factors causing undue burdens of stress, which particularly affect marginalized communities and younger generations, we can begin to address premature biological aging and the comorbid conditions it accompanies.